1961
DOI: 10.1139/v61-076
|View full text |Cite
|
Sign up to set email alerts
|

THE THERMAL NEUTRON FISSION YIELDS OF U233

Abstract: Using the mass spectrometer and isotope dilution technique, 27 cumulative fission yields from the thermal neutron fission of U233 along with 13 other fission product chains relative to each other have been determined. After normalization of the latter, values are obtained for all but seven fission decay chains whose yields are in excess of 0.5y0. INTRODUCTIONNunlerous studies have been made of the thermal neutron fission yields of Uz3. Katcoff (1) has su~llinarized the worlc preceding 1958, but since this time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1962
1962
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…For a given atomic number fine strueture would appear to become greater as the mass of the fissioning nuclide increases. (The same trend has also been observed in the thermal neutron induced fission of ^sau [15], 235u [iß] and 239Pu [17], 24iPu [18] pairs.) It is seen from Fig.…”
Section: Table 2 the Independent Yield For '^Xe From 148 Mev Neutrosupporting
confidence: 72%
See 1 more Smart Citation
“…For a given atomic number fine strueture would appear to become greater as the mass of the fissioning nuclide increases. (The same trend has also been observed in the thermal neutron induced fission of ^sau [15], 235u [iß] and 239Pu [17], 24iPu [18] pairs.) It is seen from Fig.…”
Section: Table 2 the Independent Yield For '^Xe From 148 Mev Neutrosupporting
confidence: 72%
“…1 that target nuelides with dilferent atomic number (Z) give rise to a prominence of fine strueture which appears to increase with decreasing Z. Although [18] than in ^^U [15] and it occurs to about the same extent within the [16] -2«Pu [18] and 233U [15] -^sspu [17] pairs. Before further attempts are made to relate the results summarised in Fig.…”
Section: Table 2 the Independent Yield For '^Xe From 148 Mev Neutromentioning
confidence: 99%
“…For comparison, the results from the GEF 2021/1.1 model [26] are plotted on the left panels by the blue solid step lines. The experimental data [15][16][17][18][19][20][21][22][23][24][25] from the EXFOR library are denoted by different symbols as indicated in Fig. 5.…”
Section: From Pre-to Post-neutron Emission Fpymentioning
confidence: 99%
“…We thus make assumptions for the probability in three different ways based on the experimental neutron multiplicity data. The POST-FPYs calculated by using the assumptions are compared with the POST-FPYs from the experimental data [15][16][17][18][19][20][21][22][23][24][25], the ENDF/B-VII.1 [1], and the GEF [26]. It is shown that the PRE-and POST-FPYs calculated by using the assumptions based on the experimental neutron multiplicity data can reproduce both PRE-and POST-FPY experimental data consistently.…”
Section: Introductionmentioning
confidence: 99%
“…Before Ire le&ned of Walker ' s work, we a l s o had assumed t h a t t h e most recent r e s u l t s of the mass-spectrometer groups (4,18,27,29) represent t h e most r e l i a b l e d a t a and had selected these yields as the b a s i s f o r our "best values". For convenience, these selected y i e l d s a r e l i s t e d again i n Table 3 of the Appendix, and a r e plotted i n Fig.…”
Section: Summary Of Published Valuesmentioning
confidence: 99%